Financial Transaction Digitalization, Velocity of Money, Monetary Policy, and Inflation in Indonesia: Financial Transaction Digitalization, Velocity of Money, Monetary Policy, and Inflation in Indonesia - dwi hermawan (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam UIN Datokarama Palu, 2026)
This study aims to calculate and analyze the influence of digitization of financial transactions, the speed of money circulation, and monetary policy on inflation in Indonesia in 2017–2024. The data used is quantitative secondary data obtained from the publications of Bank Indonesia (BI), the Central Statistics Agency (BPS), the Financial Services Authority (OJK), and other related institutions. Data processing was carried out using SPSS (Statistical Package for the Social Sciences) software through regression analysis and statistical tests to understand the relationship between variables. The results of the analysis show that: (1) the digitization of financial transactions has a negative and significant effect on inflation, (2) the speed of money circulation has a positive and significant effect on inflation, and (3) the monetary policy implemented by Bank Indonesia has a negative and significant effect on inflation during the study period. Interest rate adjustments and wise liquidity management have been proven to help maintain price stability and control inflation. The increasing digitization of financial transactions and flexible and responsive monetary policies play an important role in keeping inflation under control. Nevertheless, this study has limitations regarding the number of variables and the data period used. Therefore, future research is suggested to add relevant variables and extend the analysis period to obtain more comprehensive results